Medical oncology in India: Workload, infrastructure, and delivery of care - Sengar, Manju; Fundytus, Adam; Hopman, Wilma M.; Malhotra, Hemant; Gupta, Sudeep; Pramesh, C S; Hammad, Nazik; Sullivan, Richard; Vanderpuye, Verna; Seruga, Bostjan; Lopes, Gilberto; Brundage, Michael D.; Booth, Christopher M. (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: The growing burden of cancer within India has implications across the health system including operational delivery of cancer care and planning for human health resources. Here, we report the Indian results of a global survey of medical oncology (MO) workload in comparison to medical oncologists (MOs) in other low-middle- income countries (LMICs). Methods: An online survey was distributed through a snowball method through national oncology societies to chemotherapy-prescribing physicians in 22 LMICs. The survey was distributed to Indian MOs by the Indian Society of Medical and Pediatric Oncology and the National Cancer Grid of India. The workload was measured as the annual number of new cancer patient consults seen per oncologist. Results: One hundred and forty-seven oncologists from LMICs completed the survey; 82 from India and 65 from other LMICs. About 59% (48/82) of Indian MOs reported working exclusively in the private health system compared to 23% (15/65) of MOs in other LMICs (P < 0.001). The median number of annual consults per MO was 475 in India compared with 350 in other LMICs. The proportion of MOs seeing >1000 new consults/year was 24% (20/82) in India and 20% (13/65) in other LMICs (P = 0.530). The median number of patients seen in a full-day clinic was 35 in India and 25 in other LMCs (P = 0.003); 26% of Indian MO reported seeing >50 patients per day. Compared to other LMICs, Indian MOs worked more days/week (median 6 vs. 5, P < 0.001) and hours/week (median 51–60 vs. 41–50, P = 0.004) and had less annual leave for vacation (3 weeks vs. 4, P = 0.017). Conclusion: Indian MOs have higher clinical volumes and workload than MOs in other LMICs and substantially higher workload than MOs in high-income countries. Indian health policymakers should consider alternative models of care and increasing MO workforce supply to address the growing burden of cancer.
Keywords: Cancer care; medical oncology; oncology workload